2010
DOI: 10.1177/0022034510374056
|View full text |Cite
|
Sign up to set email alerts
|

Early Dexamethasone Relieves Trigeminal Neuropathic Pain

Abstract: The analgesic effects of dexamethasone on neuropathic pain have been controversial. The present study investigated the effects of dexamethasone on mechanical allodynia in rats with mal-positioned dental implants. Under anesthesia, the left mandibular second molar was extracted and replaced by a miniature dental implant to injure the inferior alveolar nerve. Nociceptive behavior was examined on each designated day after surgery. Mal-positioned dental implants significantly decreased air-puff thresholds both ips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 23 publications
5
33
0
1
Order By: Relevance
“…Recently, Han et al reported that early treatment with dexamethasone produces a prolonged inhibition of mechanical allodynia in a rat model of trigeminal neuropathic pain produced by mal-positioned dental implants [10]. Daily treatment with dexamethasone significantly reduced the expression of p-p38 MAPK and p-NF-κB on POD 7 in our present experiments.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, Han et al reported that early treatment with dexamethasone produces a prolonged inhibition of mechanical allodynia in a rat model of trigeminal neuropathic pain produced by mal-positioned dental implants [10]. Daily treatment with dexamethasone significantly reduced the expression of p-p38 MAPK and p-NF-κB on POD 7 in our present experiments.…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, similar results were obtained with the daily treatment with Dex after CION. Our results are in agreement with Han and co-workers, which also showed that early, but not the late, treatment with Dex at much higher doses reduced the mechanical hyperalgesia induced by malpositioned dental implant (Han et al, 2010). Since it has been shown that Dex acts by blocking the synthesis of cytokines (Safieh-Garabedian et al, 1995), we evaluated if the de novo cytokine synthesis occurs only at the beginning or later after neuropathic pain induction.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, application of a long-acting anti-inflammatory drug diprospan in treating primary TN through local nerve cord injection has achieved satisfactory effects [1][2][3][4] . However, the action mechanism of this agent and the pathophysiological changes in the trigeminal nerve remain unclear.…”
mentioning
confidence: 99%
“…However, the action mechanism of this agent and the pathophysiological changes in the trigeminal nerve remain unclear. Some studies suggested that the anti-inflammatory, anti-rheumatic, and anti-anaphylactic properties of disprospan were involved [1,2] . In this study, rat model of TN was established by inducing chronic constriction injury (CCI) to the left trigeminal nerve of the rats.…”
mentioning
confidence: 99%